Monodispersed SnS nanoparticles anchored on carbon nanotubes for high-retention sodium-ion batteries. Issue 16 (8th April 2020) - Luu, Thi Hoai Thuong; Duong, Dinh Loc; Lee, Tae Hoon; Pham, Duy Tho; Sahoo, Ramkrishna; Han, Gyeongtak; Kim, Young-Min; Lee, Young Hee
Abstract : An effective approach to alleviate the volume expansion of alloying material and magnify the capacity of sodium-ions batteries anode by anchoring the SnS nanoparticles densely on porous carbon nanotubes film. Abstract : Driven by the desire to find efficient alternatives to lithium-ion batteries for large-scale energy storage systems, sodium-ion batteries (SIBs) have been extensively researched with the aim of realizing similar electrochemical properties to those of lithium. While Sn-based anodes for SIBs offer reasonable theoretical capacity (847 mA h g −1 for Na15 Sn4 ), their sluggish kinetics, low conductivity, and large volume expansion represent unresolved drawbacks. To address these issues, we propose an effective approach to alleviate the volume pulverization and enhance the capacity of SIB anodes by anchoring SnS nanoparticles densely on a porous carbon nanotube (CNT) film (SnS@CNT). As a result of the formation of inherent chemical bonds between SnS and the surface of the CNTs, the well-dispersed SnS nanoparticles anchored on the CNT network help to significantly enlarge the contact surface area between the active material and sodium ions. This free-standing film yields a high capacity of up to 762 mA h g −1, owing to its improved conductivity and enlarged surface area, which are attributed to the increase in capacity of 146%, compared to the capacity of SnS nanoparticles in the absence of CNT (521 mA h g −1 ), at a current density of 100 mA g −1 . The SnS@CNT anode exhibits excellent cyclability at a current density of 1 A g −1, with capacities of 666 and 615 mA h g −1 after 100 (100% retention) and 500 cycles (92% retention), respectively, in addition to excellent kinetics. The hybrid SnS@CNT film used as the SIB anode is binder-free, allowing for a greater concentration of active materials that contribute to battery performance.